2014
DOI: 10.1177/0018720814545515
|View full text |Cite
|
Sign up to set email alerts
|

Situation Awareness Measures for Simulated Submarine Track Management

Abstract: Defense researchers have identified SPAM as an alternative to SAGAT because it would not require field exercises involving submarines to be paused. SPAM was not disruptive, but it is potentially problematic that SPAM did not predict variance in all three performance tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 23 publications
6
64
0
Order By: Relevance
“…Track management requires a console operator to coordinate analysis of the output from the submarine's passive sonar (i.e., "tracks") in order to determine the range, course, and speed of potential "contacts" detected at sea (a process referred to as contact localization). The current paper extends prior research that has examined SA in submarine track management (Loft, Bowden, et al, 2015;Loft, Morrell, & Huf, 2013;Loft, Sadler, Braithwaite, & Huf, 2015) by examining how SA, workload, and performance in track management are affected by manipulations of uncertainty in the location of contacts. This manipulation has applied relevance because the location of contacts in submarine control rooms can be uncertain due to the limitations of passive sonar and deception by hostile forces (Kirschenbaum, Trafton, Schunn, & Trickett, 2014;Stanton, 2014).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Track management requires a console operator to coordinate analysis of the output from the submarine's passive sonar (i.e., "tracks") in order to determine the range, course, and speed of potential "contacts" detected at sea (a process referred to as contact localization). The current paper extends prior research that has examined SA in submarine track management (Loft, Bowden, et al, 2015;Loft, Morrell, & Huf, 2013;Loft, Sadler, Braithwaite, & Huf, 2015) by examining how SA, workload, and performance in track management are affected by manipulations of uncertainty in the location of contacts. This manipulation has applied relevance because the location of contacts in submarine control rooms can be uncertain due to the limitations of passive sonar and deception by hostile forces (Kirschenbaum, Trafton, Schunn, & Trickett, 2014;Stanton, 2014).…”
Section: Introductionmentioning
confidence: 65%
“…Participants also responded to SPAM queries. Loft et al (2013) and Loft, Bowden, et al (2015) found that SPAM predicted variance in performance after SPAM accept time had been statistically controlled. Loft, Bowden, et al (2015) extended Loft et al (2013) by showing that SPAM can predict incremental variance in performance after controlling for subjective measures of SA and subjective workload and that administering SPAM queries does not negatively affect performance or subjective workload.…”
Section: Domain Background and Sa Theory And Measurementmentioning
confidence: 99%
“…Understanding how instruments, sensors and interfaces facilitate the generation of a tactical picture during submarine operations is a challenge due to the complexity of sociotechnical systems (Loft, Bowden, Braithwaite, Morrell, Huf, & Durso, 2015;Huf, Arulampalam, Masell, Tynan, Brown, Manning, 2004;Stanton, & Bessell, 2014). The current work has provided empirical evidence for clear delineations between submarine command team operators in terms of social, information and task network analysis.…”
Section: Discussionmentioning
confidence: 87%
“…The social, information and task networks demonstrate the complexities involved when completing submarine INSOs (Loft, Bowden, Braithwaite, Morrell, Huf, & Durso, 2015;Loft, Sadler, Braithwaite, & Huf, 2015;Stanton, & Bessell, 2014;Huf, Arulampalam, Masell, Tynan, Brown, Manning, 2004). The current work offers support for previous work examining submarine operations from a sociotechnical perspective (Stanton, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The area that emerged as the research background of SA is aviation system. As the area of dynamic system was expanded as time went on, studies have been carried out in various areas including automobile (Ma and Kaber, 2005), submarine (Loft et al, 2013) and army land battle situations (Riley et al, 2006), as well as airplane. Researches to measure SA in various situations from full-manual system in which humans perform all jobs to full-automation in which systems carry out all functions have been conducted, as Level 2 SA is defined as understanding factors as a whole one picture, based on factors perception.…”
Section: Introductionmentioning
confidence: 99%